Sosialisasi Pemanfaatan Bunga Telang Sebagai Inovasi Produk Lokal Baru di Desa Japanan - Fajar Cahya Putra; Syamsul Huda; Anisa Fitriau Tami (Jurnal Informasi Pengabdian Masyarakat, 2023)
This journal presents a community engagement project focused on increasing awareness and promoting the utilization of butterfly pea flowers as a new innovation for local products in Japanan Village. The objective of this project is to conduct socialization activities to introduce and educate the community in Japanan Village about the potential benefits and processing of butterfly pea flowers. The methods used include lectures, demonstrations, and interactive discussions with participants involved in these socialization activities. Through these activities, the project aims to enhance the community's understanding of the economic and health benefits associated with butterfly pea flowers. This initiative encourages collaboration among community members, local businesses, and relevant stakeholders to explore opportunities for sustainable production and commercialization of butterfly pea flower-based products. The results of this project show promising outcomes, as the community demonstrates increased awareness and interest in utilizing butterfly pea flowers in their daily lives and entrepreneurial efforts. This journal provides insights into the process and impact of socialization activities centered around the utilization of butterfly pea flowers as a new innovation for local products.